Principles of measurement systems - Bentley, John P., 1943- (Harlow, England ; New York : Pearson Prentice Hall, 2005)
'Principles of Measurement Systems' treats measurement as a coherent and integrated subject. Looking at sensing, signal conditioning, signal processing, and data presentation, it offers a rounded discussion of the fundamentals of accurate measurement of all kinds of activity.
Includes bibliographical references and index.
Keywords: Physical instruments; Physical measurements; Engineering instruments; Automatic control